2019
DOI: 10.1039/c9nr00446g
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into semicrystalline states of electrospun nanofibers: a multiscale analytical approach

Abstract: For potential applications in the biomedical domain, we report a comprehensive roadmap towards structural hierarchy and anisotropy in electrospun fibers based on scattering and diffraction studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 60 publications
2
35
1
Order By: Relevance
“…On the contrary, the flatter the curve, the higher the degree of alignment. As a further proof, the similarity between the curves corresponding to the membranes collected at 1000 and 1500 rpm confirm what has been reported in [69], where the analysis of SEM-micrographs as well as Small Angle X-ray scattering (SAXS) have shown that these two membranes have a comparable degree of alignment. Interestingly however, we show here that although the membrane collected at 1000 rpm displays an anisotropic behavior that is similar to that of the membrane collected at 1500 rpm (see the similar trends of the corresponding curves in Fig.…”
Section: Correlations Between the π L (ρ φ)-Images And The Membranessupporting
confidence: 88%
See 4 more Smart Citations
“…On the contrary, the flatter the curve, the higher the degree of alignment. As a further proof, the similarity between the curves corresponding to the membranes collected at 1000 and 1500 rpm confirm what has been reported in [69], where the analysis of SEM-micrographs as well as Small Angle X-ray scattering (SAXS) have shown that these two membranes have a comparable degree of alignment. Interestingly however, we show here that although the membrane collected at 1000 rpm displays an anisotropic behavior that is similar to that of the membrane collected at 1500 rpm (see the similar trends of the corresponding curves in Fig.…”
Section: Correlations Between the π L (ρ φ)-Images And The Membranessupporting
confidence: 88%
“…The membranes consisting of nanofibers in this study were produced by electrospinning technique, using a custom-built device: the production and characterization of these membranes are thoroughly described in [69]. In brief, pellets of PVDFhfp of molecular weight of ∼ 400000 g.mol −1 were dissolved in a concentration of 35 % w/v in dimethylfomamide (DMF).…”
Section: Probed Samples: Electrospun Pvdfhfp Membranes With Varying Dmentioning
confidence: 99%
See 3 more Smart Citations